Evaluation of pharyngeal airway changes & velopharyngeal function following Le-fort I osteotomy in cleft lip and palate patients- a systematic review & meta analysis - Eldo Babu; Parvathy Ghosh; K. Sarika; Anju James; N.K. Sapna Varma; V.V. Ajith (Journal of Oral Biology and Craniofacial Research)
Background: Le-Fort I osteotomy is commonly performed in cleft lip and palate patients to correct maxillary discrepancies, potentially influencing pharyngeal airway dimensions and velopharyngeal function. Thus, the review aims to evaluate the effects on pharyngeal airway and velopharyngeal function following Le-Fort I osteotomy in cleft lip and palate patients. Method: This systematic review followed the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). A comprehensive electronic search in databases of Scopus, EBSCO, PubMed, Cochrane, CINAHL, ScienceDirect and Google Scholar was performed to identify studies published from inception to August 2024 with language restricted to English. The critical appraisal using NIH quality assessment tool and data extraction processes were carried out independently by two reviewers. A meta-analysis was conducted to determine the effects of Le-Fort I on nasopharyngeal, oropharyngeal and hypopharyngeal airway depth before and after the intervention. Quality was evaluated using GRADE. Results: Twelve articles were included in this review. Le-Fort I maxillary advancement significantly increases pharyngeal airway dimensions, particularly in the nasopharyngeal and oropharyngeal regions, with most studies reporting improved airway space postoperatively. However, velopharyngeal function outcomes were variable: some patients experienced transient increases in nasalance or hypernasality, while others showed no significant adverse effects. Notably, preoperative hypernasality may predict postoperative velopharyngeal insufficiency. Conclusion: Le-Fort I maxillary advancement increases pharyngeal airway volume; particularly in the nasopharyngeal and oropharyngeal regions; thereby improving breathing function, especially during sleep. However, the degree of airway expansion varies depending on the extent of surgery and preoperative airway conditions. While the procedure often enhances velopharyngeal closure by improving anatomical alignment and muscle coordination, it also carries a risk of worsening velopharyngeal insufficiency if the maxilla is advanced beyond a certain limit, which differs among individuals.